The Existence of Islamic Banking in Indonesia from Non-Muslims Perceptions - Setiawan, Budi; Puspitasari, Ratih; Manurung, Tarida Marlin Surya (ASEAN Marketing Journal, 2021)
This study has three main objectives, which are to identify the common knowledge of the non- Muslims on the Islamic banking products and services; to identify the non-Muslims perception; and to analyze the influence of respondents’ demography to the perception on revenue sharing system of Islamic banking. E-survey method was used with a quantitative approach involving 244 respondents, who partook to fill the online questionnaire. Descriptive statistics and binary logistic regression tests were used as data analysis techniques. The majority of the respondents have a better knowledge on savings, rather than other products. The existence of Islamic banking has been able to attract the public attentions, and not contrary to their religious beliefs. Respondent’s demography (ie: gender, age, level of formal education) significantly influences respondent’s perception on revenue sharing system of Islamic banking in Indonesia.